Harlan Hubbard : life and work - Berry, Wendell, 1934- (Blazer lectures, 1990)
Berry chronicles the lives of Harlan Hubbard, with his wife Anna, as they lived on a houseboat for several years and later in a small cabin on the banks of the Ohio River. Their earthy and calm philosophy was expressed through Harlan's long-running journal and his paintings.